2000
DOI: 10.1084/jem.191.5.771
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Defects in Natural Killer and Memory Cd8 T Cell Lineages in Interleukin 15–Deficient Mice

Abstract: C57BL/6 mice genetically deficient in interleukin 15 (IL-15−/− mice) were generated by gene targeting. IL-15−/− mice displayed marked reductions in numbers of thymic and peripheral natural killer (NK) T cells, memory phenotype CD8+ T cells, and distinct subpopulations of intestinal intraepithelial lymphocytes (IELs). The reduction but not absence of these populations in IL-15−/− mice likely reflects an important role for IL-15 for expansion and/or survival of these cells. IL-15−/− mice lacked NK cells, as asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
1,364
5
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,457 publications
(1,455 citation statements)
references
References 41 publications
(44 reference statements)
66
1,364
5
2
Order By: Relevance
“…Although the importance of IL-15 in this process is undisputed [19,20,[22][23][24], it is unclear whether IL-15 1) acts on early NK cell precursors, 2) is only needed at the terminal steps of NK cell development or 3) is important role in maintaining lymphocyte proliferation and homeostasis. To investigate this process, we cultured human umbilical cord blood (UCB) CD34 + Lin − CD38 − primitive progenitors on AFT024.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the importance of IL-15 in this process is undisputed [19,20,[22][23][24], it is unclear whether IL-15 1) acts on early NK cell precursors, 2) is only needed at the terminal steps of NK cell development or 3) is important role in maintaining lymphocyte proliferation and homeostasis. To investigate this process, we cultured human umbilical cord blood (UCB) CD34 + Lin − CD38 − primitive progenitors on AFT024.…”
Section: Resultsmentioning
confidence: 99%
“…IRF-1 knockout mice exhibit a severe NK deficiency, which is mediated by failure of transcriptional regulation of IL-15. In addition, knockout mice deficient in IL-15 itself or IL-15Rα have very few NK cells while IL-2 and IL-2Rα knockouts are unaffected [19,20]. In human studies, IL-15 is made by stroma and macrophages [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mice deficient for signalling components of IL-7 and IL-15 (IL-7Ra À/À IL-2Rb À/À display a thymopoiesis block more closely resembling that of g c À/À mice than mice deficient for signalling components of IL-7 and IL-2 (IL-7Ra À/À IL-2Ra À/À ) or IL-7 and IL-4 (IL-7Ra À/À IL-4Ra À/À ) [39]. That fact that mice deficient for IL-15 or IL-15Ra display no obvious abnormalities in thymopoiesis [20,21] suggests a minor role for IL-15 in this species that is only evident when thymopoiesis is already impaired (such as in the absence of IL-7). The bioactive form of IL-15 is complexed with the IL-15Ra chain.…”
Section: Discussionmentioning
confidence: 99%
“…While IL-15 does not appear essential for thymopoiesis in mice [20,21], previous studies have shown that TEC subsets express IL-15 [22] and could ''trans-present'' IL-15/IL-15Ra complexes to developing thymocytes [23,24]. Since the bioavailability of human IL-15 in HIS mice appears limited [3], we next investigated the effect of exogenous IL-15 on human thymopoiesis in vivo.…”
Section: Effects Of Exogenous Human Il-15 Administration On Human Thymentioning
confidence: 99%
“…IL-15 was initially identified as a cytokine that could support the proliferation of an IL-2 dependent cell line in the presence of neutralizing antibodies against IL-2 [103,104]. Some similarities in the in vitro activities of IL-2 and IL-15 are mediated by a shared receptor subunit [105]; however studies in mice lacking IL-15 [106] or IL-2 [107] suggest that the two cytokines mediate distinct biological functions [108]. Similar to IL-2, IL-15 can mediate differentiation of NK cells as well as drive the proliferation of naïve T cells [108].…”
Section: Rantesmentioning
confidence: 99%